Key opinion leaders' guide to spinning a disappointing clinical trial result. (13th December 2018) - Hartley, Adam; Shah, Mit; Nowbar, Alexandra N; Rajkumar, Christopher; Howard, James P; Francis, Darrel P
Abstract : Adam Hartley and colleagues present a playbook for commenting on trials with disappointing results